Internetnutzung in der deutschen Agrarwirtschaft: Online-Handelsportale als neue Organisationsform; Utilisation of the internet in German agriculture: E-hubs as a new form of organization - Andreas Boc̈ker; Claus Brodersen (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– This paper describes the concept of E-commerce portals, so called E-hubs, in its basic characteristics and analyses their potential impacts on agribusiness enterprises and agricultural markets. Since these impacts depend on the level of market penetration of this new type of organisation, it is further attempted to identify the most relevant factors that determine future acceptance and utilisation of internet portals at sector and enterprise level.
Keywords: 330; Landwirtschaft; Internet; Electronic Commerce; Ostdeutschland